An Evaluation of Different Mulches Used in Soil Moisture Conservation of Coconut Lands - Arachchi, L. P. Vidhana (International Coconut Community Journal, 1998)
An investigation on the ability ofdifferent types of mulches to conserve soil moisture and their effect on coconutpalm (Dwarfx Tall; CRIC 65) was carried out in Madampe soil series at Bandirripuwa Estate, Lunuwila located in agro ecological region of IL3 of Sri Lanka. Different types ofmulches compared in this study were dried coconut fronds and leaves, cover crop with Pueraria phasioloides and Brachiaria milliformis versus bare soil (Control). Soil moisture status was monitored using the neutron scattering technique. Leaf water potential of coconut with respect to different treatments was also monitored during dryperiod. Results showed that Brachiaria milliformis and Pueraria phasioloides extracted significantly (p<0.001) more waterfrom soils than diied mulch and the control. The amount of water extracted in the above treatments were 74.4Yo, 62.5Yo, 59.79yo and 61.3% respectively. However, the extraction was not significantly different when the rainfall was greater than 100 mm. About 33 mm of water retained in Brachiaria milliformis introduced soil profiles even by the end of dry period Water losses by Pueraria phasioloides grown plots, specially through evapotranspiration, were 1higher in initial stages of the dry period, but later stage losses were lower than that of Brachiaria due to defoliation of Pueraria leaves during severe dry period Leaf water potential of coconut with respect to stress conditions of different treatments revealed that Pueraria phasioloides and Brachiaria milliformis did not adversely affect coconut palm grown in Madampe series, although those live materials extracted more waterfrom soilprofile compared to the other treatments. In general, dry mulching wasfound to be the most efficient moisture conservative practice that can be adopted for coconut lands.